Some Objective Reasons why the State Language Policy is Moderate in Kazakhstan (International relations and international law Journal, 2016)
This article dwells upon some objective reasons why the state language policy in the Republic of Kazakhstan was and is still moderate. What should be done on the part of the government, individuals, language centers for the development and advancement of the Kazakh language? What kind of responses should be from the other ethnicities to the initiatives on the formulation of the language policy, in particular, the state language policy? There are a variety of view-points on this issue. Once Henry Ford said: «Coming together is a beginning, staying together is progress and working together is success». That’s why if we want to be successful in the formation of the state language policy and effectively to implement it, we should work together and learn the Kazakh language and recognize it as a state language.
Keywords: the Cyrillic Alphabet; the Latin script; objective reasons; component; an integral part